Policy Feedback and the Politics of Administration. (16th April 2014) - Soss, Joe; Moynihan, Donald P.
<x xml:space="preserve">Abstract</x> This article surveys the policy feedback framework developed in political science and clarifies its implications for public administration. A feedback perspective encourages us to ask how policy implementation transforms the webs of political relations that constitute governance. Administrators play a key role in shaping the political conditions of bureaucratic performance and the organization of power in the broader polity. At the same time, this perspective underscores that policies are more than just objects of administrative action. Policies are political forces in their own right that can alter key components of administration, including phenomena such as organizational capacity, structures, routines, authorities, motivations and cultures. These sorts of administrative themes have received little attention in policy feedback research, just as the political effects of policies have been overlooked in public administration studies. Bridging these perspectives offers a basis for exciting new agendas and advances in public administration research.